Pressure drop in two phase slug/bubble flows in mini scale capillaries - Walsh, E; Muzychka, Y; Walsh, P; Egan, V; Punch, J (2009)
A segmented two phase slug/bubble flow occurs where a liquid and a gas are pumped into the same tube over a range of Reynolds numbers. This segmented two phase flow regime is accompanied by an increase in pressure drop relative to the single phase flow where only one fluid is flowing in a capillary. This work experimentally and theoretically examines the pressure drop encountered by the slug/bubble flow with varying slug lengths in mini channels. In the experimental work the dimensionless parameters of Reynolds number and Capillary number span over three orders of magnitude, and dimensionless slug length ranges over two orders of magnitude to represent flows typical of mini- and micro-scale systems. It is found, in agreement with previous work, that these dimensionless groups provide the correct scaling to represent the pressure drop in two phase slug/bubble flow, although the additional pressure drop caused by the interface regions was found to be ∼40% less than previously reported. © 2009 Elsevier Ltd. All rights reserved.